Influence of Monobloc/Le Fort III Surgery on the Developing Posterior Maxillary Dentition and Its Resultant Effect on Orthognathic Surgery. Issue 2 (24th November 2020) - Yang, Robin; Shakoori, Pasha; Lanni, Michael A.; Nah, Hyun-Duck; Scott, Michelle; Swanson, Jordan W.; Bartlett, Scott P.; Taylor, Jesse A.
Abstract : Background: Timing of frontofacial surgery for the syndromic craniosynostosis as it relates to various surgical risks has not been adequately studied. The purpose of this study was to investigate posterior dental complications of midface advancement in patients with syndromic craniosynostosis undergoing surgery at different ages and the effects on subsequent orthognathic surgery. Methods: A retrospective chart review of patients with syndromic craniosynostosis treated with midface advancement (monobloc or Le Fort III) from 1999 to 2018 was carried out. Patient demographics, records, and imaging studies were reviewed. A subanalysis of those patients who were also treated with orthognathic surgery from 2014 to 2018 with imaging studies available for analysis was also performed. Results: Thirty-seven patients met the inclusion criteria. Sixty-four percent of the patients had radiographic evidence of maxillary molar dental abnormality. Older age at the time of surgery was significantly associated with a lower odds of sustaining dental injury (OR, 0.55; p = 0.034). The odds of damaging second or third maxillary molars was significantly higher with a younger age at the time of surgery ( p = 0.021 and p = 0.034). The odds of sustaining dental injury increased moving posteriorly, showing the risk of abnormal pattern of M3 greater than M2 greater than M1. Advanced age at the time of surgery was significantly associated with decreased odds of dental injury (OR, 0.55; p = 0.034). Conclusions: Damage to the developing permanent maxillary molars may affect orthodontic management, mastication, and potentially maxillary development. Delaying frontofacial surgery until development of the permanent maxillary dentition should be considered if other indications do not mandate earlier intervention.